Editorial: Students with Disabilities in Higher Education - Geert Van Hove; Alice Schippers; Minne Bakker (Social Inclusion, 2018)
This editorial will at first present the thirteen different articles published in the issue. On a second level, we will focus on “overarching themes”. Those themes should be understood as links between the different articles in this volume.